Diverse and abundant multi-drug resistant E. coli in Matang mangrove estuaries, Malaysia - Ghaderpour, Aziz; Ho, Wing Sze; Chew, Li-Lee; Bong, Chui Wei; Chong, Ving Ching; Thong, Kwai-Lin; Chai, Lay Ching (Frontiers in Microbiology, 2015)
E. coli, an important vector distributing antimicrobial resistance in the environment, was found to be multi-drug resistant, abundant and genetically diverse in the Matang mangrove estuaries, Malaysia. One-third (34%) of the estuarine E. coli was multi-drug resistant. The highest antibiotic resistance prevalence was observed for aminoglycosides (83%) and beta-lactams (37%). Phylogenetic groups A and B1, being the most predominant E. coli, demonstrated the highest antibiotic resistant level and prevalence of integrons (integron I, 21%; integron II, 3%). Detection of phylogenetic group B23 downstream of fishing villages indicates human fecal contamination as a source of E. coli pollution. Enteroaggregative E. coli (1%) were also detected immediately downstream of the fishing village. The results indicated multi-drug resistance among E. coli circulating in Matang estuaries, which could be reflective of anthropogenic activities and aggravated by bacterial and antibiotic discharges from village lack of a sewerage system, aquaculture farms and upstream animal husbandry.